Social Capital and Innovation as Competitive Advantage of Creative Industry in Boosting Market Share - Ribek, Pande Ketut; Suprapti, Ni Wayan Sri; Giantari, I. Gusti Ayu Ketut; Sukaatmadja, I Putu Gde (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
This study aims to determine social capital and innovation in increasing competitive advantage to achieve marketing performance in the traditional sculpture industry in Indonesia. The quantitative method with the population in this study is a sculpture entrepreneur in Gianyar and a sample of 130 entrepreneurs. The analysis technique uses SEM-PLS 3.0. The results of the study show that social capital and continuous innovation have a positive and significant effect on competitive advantage, social capital has a non-significant positive effect on marketing performance, innovation has an insignificant positive effect on marketing performance, competitive advantage has a significant positive effect on marketing performance, competitive advantage fully mediates social capital.